Question 23

Thursday, November 26, 2009
Write a subtraction statement involving two negative fractions or negative mixed fractions so that the difference is -4/3.

So basically, it's a - b= -4/3.

You can just inverse the statement and make it -4/3 + b = a. B and A have to both be negatives so for B, I just chose a random negative fraction like -2/5.

-4/3 + (-2/5) = a

When I did this, a came out as -26/15.
So it's -4/3 + (-2/5) = -26/15.

If you make it back to a - b = -4/3, it'd become -26/15 - (-2/5) = -4/3. I even checked it. It's right.

I wasn't sure if it might work with other negative fractions so I tried it with -6/7.

-4/3 + (-6/7) = a

It came out as -4/3 + (-6/7) = -46/21.

I made it back to a - b =-4/3 again. It became -46/21 -(-6/7) = -4/3. It also works.

I'd make pictures but my paint isn't being cooperative with me and neither are my cameras. I'll try again tomorrow though...

Answering Mr. Backe's question, I think it will work everytime because it's a - b = -3/4, right? A and B have to be negatives. So when you inverse the statement to -3/4 + b = a, it should work because A has to be a negative and a negative plus a negative equals a negative.

3 comments:

Mr. B. said...

Thanks Aleiah. Do two fraction questions prove your conjecture? Will it always work?

simran 9-05 said...

Great post Aleiah! You were right when you called it inverse. Your examples were really good, and good job explaining it.

kristin9-05 said...

Nice post Aleiah! You really explained that well and your examples were easy to understand.

Post a Comment